Recovering for Psychological Injuries by Invasion of Privacy in Anglo-American and Russian Legal Practice - N. S. Izmailova (Московский журнал международного права, 2008)
Recovering damages for psychological injuries is a special means of legal relief in case of violation of personal non-proprietary rights. Invasion of privacy is one of torts for which such a relief can be sought. However, the character of its application differs from country to country, which can be seen on the example of Anglo-American and Russian legal practice.Extensive practice of recovering damages for psychological injuries by invasion of privacy in Great Britain and USA has developed due to long-established system of precedents in this field. In contrast, Russia lacks the appropriate experience and thus must apply to foreign expertise in this matter.From the point of practical legal application of recovering damages for psychological injuries by invasion of privacy two essential issues concern the grounds for recovery and the criteria for defining the amount of the damages sought. The article deals with detailed analysis of these issues relating to Anglo-American and Russian experience and contains recommendations that may promote more successful application of recovering damages for psychological injuries by invasion of privacy in Russian domestic legal practice.